Factor Analysis and Reliability of the Pro-Lockdown Compliance Scale - Joy, Lijo Kochakadan; Ramachandran, Manu; Fenn, Jessy; Tan, Chee-Seng (UI Scholars Hub, 2023)
A multilevel lockdown was introduced during the COVID-19 pandemic worldwide. This new experience, however, received mixed responses from the public in different countries including India. A quantitative self-report, the Pro-Lockdown Compliance Scale (Pro-LCS), was developed to help 1) the Government and enforcing agents understand the compliance level of the public and 2) researchers investigate the antecedent factors of the compliance of the lockdown measures. The initial 10 items were administered to 309 male residents in Kerala via an online survey. The responses were randomly divided and submitted to exploratory and confirmatory factor analyses. Both analyses consistently support that the scale is best represented by a 5-item unidimensional model. Moreover, the Pro-LBS also demonstrated adequate internal consistency. The preliminary findings suggest that the scale is a brief and useful tool to examine the compliance level of the lockdown measures.